Research on bending-slip rib spalling and rib stability of extra-thick hard coal wall - Bo Xue; Yan Shang; Chen Wang; Feitian Zhang; Yunfei Liu (Scientific Reports)
Abstract In response to the frequent occurrence of coal face spalling affecting the working face production during the mining of extra-thick hard coal seams, this study investigates the characteristics of typical hard coal face damage. Coal face spalling is categorized into three stages: dynamic load influence, crack propagation, and bending instability phase. Employing the Rayleigh-Ritz method and the principle of stationary potential energy in conjunction with beam plate strength theory and maximum tensile stress strength theory, a displacement formula for coal face spalling has been developed. The formula has been validated using numerical simulation software. Additionally, a three-dimensional similitude modeling experimental platform was utilized to explore the development and failure patterns of spalling. Experimental results confirm the consistency between the theoretical derivation and the observed trajectories and locations of coal face spalling movement. The findings provide a theoretical foundation and technical reference for the management and prevention of spalling in extra-thick hard coal seam faces.